Behaviour and fate of nine recycled water trace organics during managed aquifer recharge in an aerobic aquifer - Patterson, B.; Shackleton, M.; Furness, A.; Bekele, E.; Pearce, J.; Linge, Kathryn; Busetti, Francesco; Spadek, T.; Toze, S. (Elsevier Science, 2011)
The fate of nine trace organic compounds was evaluated during a 12 month large-scale laboratory column experiment. The columns were packed with aquifer sediment and evaluated under natural aerobic and artificial anaerobic geochemical conditions, to assess the potential for natural attenuation of these compounds during aquifer passage associated with managed aquifer recharge (MAR). The nine trace organic compounds were bisphenol A (BPA), 17β-estradiol (E2), 17α-ethynylestradiol (EE2), N-nitrosodimethylamine (NDMA), N-nitrosomorpholine (NMOR), carbamazepine, oxazepam, iohexol and iodipamide. In the loworganic carbon content Spearwood sediment, all trace organicswere non-retardedwith retardation coefficients between 1.0 and 1.2, indicating that these compounds would travel at near groundwater velocities within the aquifer. The natural aerobic geochemical conditions provided a suitable environment for the rapid degradation for BPA, E2, iohexol (half life b1 day). Lag-times for the start of degradation of these compounds ranged from b15 to 30 days. While iodipamide was persistent under aerobic conditions, artificial reductive geochemical conditions promoted via the addition of ethanol, resulted in rapid degradation (half life b1 days). Pharmaceuticals (carbamazepine and oxazepam) and disinfection by-products (NDMA and NMOR) did not degrade under either aerobic or anaerobic aquifer geochemical conditions (half life N50 days). Field-based validation experiments with carbamazepine and oxazepam also showed no degradation. If persistent trace organics are present in recycled waters at concentrations in excess of their intended use, natural attenuation during aquifer passage alonemay not result in extracted watermeeting regulatory requirements. Additional pre treatment of the recycled water would therefore be required.